El – classico / Aqil Hafiz Tsen Loong Tyan ...[et al.] - Tsen Loong Tyan, Aqil Hafiz; Roslan, Mohammad Shafiq; Zuraimi, Amirul Ridzwan; Azran, Muhammad Ammar Amsyar; Ahmad, Muhammad Haiqal Danish (2022)
This business is based on partnership where it consists of five (5) members which hold important positions in the company such as General Manager also acts as an Administration Manager, Marketing Manager, Operational Manager and Financial Manager. The Business capital is RM 10,000 where the total contribution of each member is RM 50,000. This company is named El Clasico with a trademark of “Classic Gentleman”. The purpose of this business is that we want to do grooming services that are done professionally by professional barbers where it gives a good quality of groom. Our service is operated from 11am in the morning until 11pm at night. So, customers have plenty of time for customers to schedule their time to go to our barbershop. El Classico is located in Jalan Susur Larkin Perdana 2, Larkin Perdana, 80350 Johor Bahru, Johor. We chose this place because this is an attractive area which is surrounded by shop lots and close to residential areas. Other than that, this place is one of the favorite places now for people who live in Johor and also a place for tourists that came to Malaysia because it is near Singapore. The services that we provide to our customer is dry cut, which we only cut and style such as middle part, undercut, uppercut, razor cut and pompadour. In addition, our service is not just a normal service that a common barber would do, but our service includes kindness, skill and the best experience for our customer to get good feedback from our customer. So, with that we may expand our business further and promote our business around Malaysia.